Pengaruh current ratio, debt to asset ratio, earning per share, dan return on asset terhadap harga saham - Meilani, Haifa Syafira; Suryaningprang, Andre; Sudaryo, Yoyo; Herlinawati, Erna; Siddiq, Andhika Mochamad (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Fundamental analysis is the underlying principle that causes changes in stock values. The purpose of this study was to examine the effect of the Current Ratio (CR), Debt to Asset Ratio (DAR), Earning Per Share (EPS), and Return On Assets (ROA) on stock prices at PT Semen Indonesia Tbk. The research sample for one company was selected through purposive sampling for 2012–2021. This research uses a quantitative approach with secondary data through the documentation method. Data were obtained from the company's official website, Indonesia Stock Exchange (IDX) platforms, and others. This study uses SPSS 25 and Microsoft Excel for descriptive and verification analysis. Based on the findings of this study, the Debt to Asset Ratio (DAR), Earning Per Share (EPS) and Return on Assets (ROA) have a significant effect on stock prices, but the Current Ratio (CR) has no significant impact on stock prices.